SEARCH FOR PENTADIYNENITRILE COMPOUND (HC5N) IN THE ATMOSPHERE OF TITAN TROUGH OBSERVATION OF ALMA - Assyafa'at, Farhan
Titan is the largest natural satellite of Saturn, with an average radius of 2575 km. Titan is the only natural satellite that has a thick and substantial atmosphere in the Solar System. Titan's atmospheric composition is dominated by N2 (nitrogen) as much as 94-98.4%, CH4 (methane) as much as 1-5.6% and H2 (hydrogen) as much as 0.1 - 0.43%. In addition to these main compounds, there are tracer species that can be grouped into three main compounds namely hydrocarbons, nitriles, and oxygen-bearing compounds. The chemical composition of the tracer species is obtained from the reaction of various kinds of compounds that already exist. The main energy source of the chemical reaction is the energy flux from the Sun, especially from ultraviolet photons. One of the tracer species that is thought to exist in the Titan atmosphere is pentadiynenitrile (HC5N). The HC5N compound has a molecular weight of 75.07 g/mol with a linear molecular structure, and it is thought to have an important implications in astrobiology. HC5N in Titan's atmosphere has been detected by Cassini-Huygens using INMS (Ion Neutral Mass Spectrometer) in the upper part of its atmosphere and obtained a mole fraction of 1 × 10-6 at an altitude of 1100 km. The search for the HC5N was carried out for the first time using the 30-m IRAM telescope in 1997-1999. From these observations, HC5N in the stratosphere was not detected, but the upper limit of its abundance was < 2 × 10-10. In this Final Project, the search for HC5N was continued using the ALMA radio telescope (Atacama Large Millimeter/ submillimeter Array), the most sophisticated radio telescope of the 21st century, with Titan being the calibrator object. Analyses a set of ALMA data indicate that the HC5N spectra were not detected in the stratosphere of Titan as well, and an upper limit of abundance of HC5N was determined to be 2 × 10-10.